Papa, please get the moon for me - Carle, Eric 1929-2021 (Little Simon, an imprint of Simon & Schuster Children's Publishing Division, 2015)
Monica's father fulfills her request for the moon by taking it down after it is small enough to carry, but it continues to change in size. Some pages fold out to display particularly large pictures
Keywords: Mondphase; Kind; Vater; Wunsch; Mond; Moon / Juvenile fiction; Toy and movable books / Specimens; Moon / Fiction; Toy and movable books; Moon; Audiobooks; Children's audiobooks; Fiction; Juvenile works; Specimens; Bilderbuch